The Effect of Foliar Application of Salicylic acid and Thiamine on the Biochimical Characteristics of Gerbera jamesonii cv. Pink elegance - M. Mansouri; M. shoor; A. Tehranifar; Y. Selahvarzi (Majallah-i ̒Ulum-i Bāghbānī, 2016)
Gerbera is one of the ten important cut flowers in terms of production and consumption in the world and Iran. In this research effects of foliar application of salicylic acid and thiamine on biochemical characteristics of gerbera flower were investigated. This experiment was conducted in a completely randomized design with four replications in the greenhouse commercial of the Golazin Maghsoud Company. Treatments were included of municipal water (control), salicylic acid 75 and 150 µM and thiamine 250 and 500 µM. Foliar application was performed with interval of two weeks in two stages. The results showed that the treatments had a significant effect on biochemical characteristics of gerbera. The greatest amount of chlorophyll a (36.6 µg/g Fw), b (17.27µg/g Fw) and total chlorophyll content (61.17 µg/g Fw) were related to Thiamine 250 µM and the highest level of carotenoids content 7.87 (µg/g Fw) was related to Thiamine 500 µM. The most reducing sugars content (181.51 mg/g Fw) reported in 75 µM salicylic acid. The highest activity of catalase and peroxidase enzyme (94.5 and 70.7 unit enzyme per minute in gram fresh weight, respectively) were related to 75 and 150 µM salicylic acid. Thus, salicylic acid and thiamine increased photosynthetic pigments, antioxidant enzyme activities.